Pengaruh Pola Asuh Otoriter dan Permisif terhadap Kenakalan Remaja berdasarkan Tinjauan Kriminologis - Bryan Idias; Irfan Hakim; Nimrod Welly Bello; Tri Susanti; Tri Widyasto Prabowo; Pietro Grassio Ekoyulio (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Juvenile delinquency is a growing social problem closely related to the socialization process within the family. Parenting styles, as agents of primary social control, play a crucial role in shaping adolescents' character, discipline, and self-control. This paper aims to analyze the influence of authoritarian and permissive parenting styles on juvenile delinquency based on a criminological perspective. This study employed a qualitative literature review, synthesizing various scientific journals and relevant references that discuss parenting styles and delinquent behavior. The study's findings indicate that authoritarian parenting has an ambivalent relationship with juvenile delinquency. High levels of control can suppress overt delinquency in the short term, but can potentially lead to emotional tension and hidden deviant behavior if not accompanied by warmth. Conversely, permissive parenting is more consistently correlated with increased juvenile delinquency due to weak boundaries and supervision, which result in low self-control and strong peer group influence. From a criminological perspective, these findings can be explained through social control theory, differential association theory, and strain theory, which emphasize the importance of social bonds, behavioral learning processes, and social pressure in the emergence of deviance. Thus, the balance between control and warmth in parenting is a key factor in preventing juvenile delinquency. This paper emphasizes that strengthening the family's function as an agent of informal social control is an essential preventive strategy in addressing juvenile delinquency.